The right word : Roget and his thesaurus - Bryant, Jen, 1960-; Sweet, Melissa, 1956- (Grand Rapids, Michigan : Eerdmans Books for Young Readers, 2014)
The story of "shy young Peter Mark Roget, [for whom] books were the best companions--and it wasn't long before Peter began writing his own book. But he didn't write stories; he wrote lists. Peter took his love for words and turned it to organizing ideas and finding exactly the right word to express just what he thought. His lists grew and grew, eventually turning into one of the most important reference books of all time"--Amazon.com.
Includes bibliographical references.
Keywords: Roget, Peter Mark, -- 1779-1869 -- Juvenile literature; Lexicographers -- Great Britain -- Biography -- Juvenile literature; Philologists -- Great Britain -- Biography -- Juvenile literature; Roget, Peter Mark, -- 1779-1869. -- Juvenile literature; Roget, Peter Mark, -- 1779-1869.; Lexicographers; Philologists; Roget, Peter Mark, -- 1779-1869.